Lumbar Vertebral Body and Disc Morphometry in Punjab - Faiza Irshad, Haroon Saeed, Sarfraz Ahmed, Amir Hussain Ashraf, Muhammad Nauman Akram, Muhammad Saad Abdullah, Mufassar Nishat, Muhammad Afzal Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background and objective: Low back pain is common in the elderly due to adaptive changes to stress and osteoporosis of the lumbar spine. Skeletal geometry varies in different population groups. Objective of this study was to record reference values of morphometric data of lumbar spine in normal adult male and female subjects of Punjab. Study design: Cross-sectional population study Material and methods: Anterior and central height and concavity index for each vertebra were measured and calculated from radiographs. Anterior and posterior height and anteroposterior diameter were measured for each disc and wedge index was calculated. Results: All parameters were significantly larger in the males as compared to the females. Significant difference was found in the anterior height of the intervertebral discs at L1-2 to L4-5 while it was insignificant at L5-S1. Posterior height of discs was significantly larger in the male group at L1-2 to L3-4. Wedge index (WI) for discs was relatively larger in the female group. Conclusion: The study has provided some reference values of measurements of lumbar spine in adult male and female population of Punjab which may be valuable for better assessments of morphological changes by the clinician and for further research in this area.